«Արարչագործության» թեման հայոց ավանդական հարսանիքի փեսայի ծիսական տեքստում - Շագոյան, Գայանե («Զանգակ - 97»)
The arlicle discusses the mythological content of the bridegroom "Ur-ritual". It is reconstructed on the base of two rituals: of shaving and dressing the bridegroom as a "king". Both of them have a context of creation, but while the ritual of shaving has the theme of world unfolding from the primordial sacrifice, the ritual of dressing implies the Integration (creation) of the First Man from the different parts of the universe. Initial unity of these riluals assumes their correlation with the mythological "creation cycle" by Bruce Lincoln.
Keywords: Ծեսեր; Ազգաբանություն